PENERAPAN KOMUNIKASI TERAPEUTIK OLEH TERAPIS PADA PASIEN ANAK PENYANDANG ADHD (ATTENTION DEFICIT HYPERACTIVITY DISORDER) DALAM MENINGKATKAN KONSENTRASI: (Studi di Klinik Tumbuh Kembang Anak Olan Development Center Sragen) - Hastuti, Widy; Hindra H, Nurnawati; Mahar Rizqi, Fikriana (Solidaritas, 2024)
Inappropriate care and education patterns for children with special needs can result in delaysand limitations in development, especially in children with ADHD (Attention DeficitHyperactivity Disorder). One of the causes is the lack of optimality in education,communication patterns and care between ADHD children and the people around them.Therefore, this research aims to explain how therapists at the Olan Development CenterSragen Child Development Clinic apply therapeutic communication to child patients who haveADHD to increase their concentration levels. The theory used is the theory of stages oftherapeutic communication by Stuart, G.W. This research uses a qualitative descriptivemethod. Data collection techniques use observation, interviews, documentation methods.Meanwhile, the data analysis techniques used are data reduction, data presentation, anddrawing conclusions. The results of this research show that in the therapy process, therapistsalways use verbal and non-verbal communication. Verbal communication takes the form ofcommands and praise, while non-verbal communication takes the form of hugs. Next, there isa therapeutic communication process carried out by the therapist which consists of theintroduction, orientation, work and evaluation stages. In its implementation, lack of completefacilities and infrastructure, limited time and parents who are less cooperative are theobstacles experienced by therapists when carrying out this process.Keywords: ADHD, Therapeutic Communication, Therapist